Disassembly of the divisome in Escherichia coli: evidence that FtsZ dissociates before compartmentalization. Issue 1 (20th February 2014) - Söderström, Bill; Skoog, Karl; Blom, Hans; Weiss, David S.; von, Gunnar; Daley, Daniel O.
Summary In most bacteria cell division is mediated by a protein super‐complex called the divisome that co‐ordinates the constriction and scission of the cell envelope. FtsZ is the first of the divisome proteins to accumulate at the division site and is widely thought to function as a force generator that constricts the cell envelope. In this study we have used a combination of confocal fluorescence microscopy and fluorescence recovery after photobleaching (FRAP) to determine if divisome proteins are present at the septum at the time of cytoplasmic compartmentalization in Escherichia coli. Our data suggest that many are, but that FtsZ and ZapA disassemble before the cytoplasm is sealed by constriction of the inner membrane. This observation implies that FtsZ cannot be a force generator during the final stage(s) of envelope constriction in E. coli.